THE IMPORTANCE OF LEXICAL COMPETENCE FROM THE PERSPECTIVE OF THE COMMUNICATIVE-COGNITIVE APPROACH - Xabibullaeva, Guljaxan Kengesbaevna (SCIENCE and SOCIETY, 2026)
The article examines the development of English lexical competence among students in grades 10-11 studying the Karakalpak language in the Republic of Karakalpakstan. The theoretical foundations of lexical competence, its structure and subcomponents (motivational, cognitive, practical, socio-cultural, reflexive) are analyzed.
Keywords: lexical competence; communicative-cognitive approach; Karakalpak; grades 10-11; English language; methodological system; interference; authentic texts; education; Karakalpakstan